Role of Wnt Signaling in Central Nervous System Injury - Lambert, Catherine; Cisternas, Pedro; Inestrosa, Nibaldo C. (My University, 2016)
The central nervous system (CNS) is highly sensitive to external mechanical damage, presenting a limited capacity for regeneration explained in part by its inability to restore either damaged neurons or the synaptic network. The CNS may suffer different types of external injuries affecting its function and/or structure, including stroke, spinal cord injury, and traumatic brain injury. These pathologies critically affect the quality of life of a large number of patients worldwide and are often fatal because available therapeutics are ineffective and produce limited results. Common effects of the mentioned pathologies involves the triggering of several cellular and metabolic responses against injury, including infiltration of blood cells, inflammation, glial activation, and neuronal death. Although some of the underlying molecular mechanisms of those responses have been elucidated, the mechanisms driving these processes are poorly understood in the context of CNS injury. In the last few years, it has been suggested that the activation of the Wnt signaling pathway could be important in the regenerative response after CNS injury, activating diverse protective mechanisms including the stimulation of neurogenesis, blood brain structure consolidation and the recovery of cognitive brain functions. Because Wnt signaling is involved in several physiological processes, the putative positive role of its activation after injury could be the basis for novel therapeutic approaches to CNS injury.
Keywords: wnt signaling; stroke; spinal cord injury; traumatic brain injury